ANALYSIS OF THE MECHANISM FOR SETTING THE PRICE OF LOCAL SALT IN THE BAITUSSALAM DISTRICT OF ACEH BESAR REGENCY ACCORDING TO THE ṠAMAN CONCEPT - Firdaus, Mirja; Sulfanwandi; T.Surya Reza (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This article analyses the mechanism of local salt pricing based on the concept of ṡaman. Local salt pricing in Baitussalam Subdistrict, Aceh Besar Regency, is currently unstable because local salt prices are determined by a combination of supply and demand, as well as other factors, resulting in prices received by farmers being unbalanced and failing to meet the aspects of price stability. From the perspective of the ṡaman concept, the government has the authority to intervene and create standard pricing policies to create price stability. This type of research is qualitative, employing an empirical juridical approach. The data sources were obtained from primary and secondary sources. The primary sources were obtained from interviews with informants. Secondary sources were obtained from studies related to this research. The findings indicate that the price of local salt in Baitussalam Subdistrict does not align with that of farmers and collectors. This is influenced by the abundance of supply and the power of collectors in the bargaining process. In this case, the absence of price standards has resulted in the price of salt for local salt farmers not reflecting the balance between production costs and selling prices. This is not in line with the perspective of ṡaman in fiqh muamalah because of the emergence of value inequality and price instability in salt sales transactions. The local government, through the Trade Office and the Marine and Fisheries Office, needs to reformulate a pricing mechanism that is more equitable and also favours local producers.